Adult onset orbital xanthogranuloma, a variant of adult orbital xanthogranulomatous disease: An infrequent entity - Satyanka Lakavarapukota; K V T Gopal; Sudhir Babu Karri; Rekha Rani Bulla (Indian Dermatology Online Journal, 2024)
Adult orbital xanthogranulomatous diseases (AOXGD) present clinically with symmetrical swellings around the eyes and are collectively considered within the broader group of non-Langerhans cell histiocytosis. A 45-year-old female presented with asymptomatic progressive, skin-colored, thick raised lesions around the eyes of 1 year duration. On dermatological examination, large indurated, lobulated, skin-colored thick plaques were seen bilaterally over infraorbital areas, along with a few hard, discrete nodules over the left infraorbital area. Histopathology showed pan-dermal infiltration with foamy histiocytes, non-lipidized histiocytes, a few multinucleate giant cells, lymphocytes, and a few plasma cells, with immunohistochemistry showing CD68 and S100 positivity. Laboratory and imaging studies did not show any abnormality. Based on the above findings and the absence of internal organ involvement, the patient was diagnosed with adult-onset orbital xanthogranuloma (AOX). The patient was treated with three monthly sessions of intralesional corticosteroid injections, along with methotrexate 12.5 mg per week for 8 weeks, resulting in a moderate reduction in the size of the plaques. The patient is under regular follow-up. The present case highlights the rare case of AOX and the importance of prompt recognition and evaluation in view of its potential hematological and systemic associations.